Impact of rapid urbanization on groundwater storage variation amid climate change in the Yangtze River Basin - W.J. Zhou; L. Hao (Journal of Hydrology: Regional Studies)
Study region: The Yangtze River Basin (YRB), China. Study focus: The escalating dependence on groundwater resources under climate change pressures is potentially exacerbated by urban expansion, which may amplify groundwater depletion risks. However, there is still a knowledge gap on the impacts of urbanization on groundwater storage (GWS) dynamics at a basin scale. This study focused to identify the impact of urbanization on groundwater storage variation across two decades (2002–2022) through analysis of GWS anomalies (GWSA) dataset derived from GRACE and GLDAS, and quantify the contribution of climate and human activities to urban GWSA applying residual analysis. New hydrological insights for the region: The results indicated that the annual urban GWSA generally remains a steady upward trend, with an increase rate of 3.5 mm yr−1. Seasonal GWSA differences between cities and croplands highlight the important effects of evapotranspiration on groundwater recharge. Climate change, especially increased precipitation (7.4 mm yr−1), is the dominant factor for the rise of urban GWSA. We conclude that, both climate and urbanization effects in the humid YRB have played a positive role in maintaining a steady upward trend in urban GWSA. Our findings provide new insights on the close connection of urbanization, watershed evapotranspiration, and groundwater. Effective basin water resource management should consider groundwater response to both urbanization and climate change.